2005
DOI: 10.1016/j.matlet.2005.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Detection of grain-boundary resistance to slip transfer using nanoindentation

Abstract: Nanoindentation measurements near a high-angle grain boundary in a Fe-14%Si bicrystal showed dislocation pile-up and transmission across the boundary. The latter is observed as a characteristic displacement jump, from which the Hall -Petch slope can be calculated as a measure for the slip transmission properties of the boundary. D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 12 publications
4
61
0
1
Order By: Relevance
“…Moreover, GB pop-ins were not observed in interstitial-free steel or in fcc copper, but were observed in commercial steel with interstitials. Soer et al 62,67 studied grain boundaries in Fe-14%Si and Mo bicrystals and reported consistent GB pop-ins in Fe-14%Si, but not in Mo. Aifantis et al 65 also reported GB pop-ins in Fe-2.2%Si bicrystals.…”
Section: Grain/phase Boundaries In Metalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, GB pop-ins were not observed in interstitial-free steel or in fcc copper, but were observed in commercial steel with interstitials. Soer et al 62,67 studied grain boundaries in Fe-14%Si and Mo bicrystals and reported consistent GB pop-ins in Fe-14%Si, but not in Mo. Aifantis et al 65 also reported GB pop-ins in Fe-2.2%Si bicrystals.…”
Section: Grain/phase Boundaries In Metalsmentioning
confidence: 98%
“…3b are referred as grain boundary (GB) pop-ins. 61,62,[64][65][66][67] These are attributed to slip transfer events at the grain boundary. These occur at significantly higher load levels (after the sample has experienced a significant amount of plasticity in the indentation zone).…”
Section: Grain/phase Boundaries In Metalsmentioning
confidence: 99%
“…This refinement considers metals with multiple types of slip systems. The purely geometric criterion (3) is applied in [47], while in [96], it is both applied and combined with investigations regarding the RBV criterion and incompatibility stresses. The importance of considering the RBV in the slip transmission prediction is emphasized in [97], as well.…”
Section: Criteria That Account For Slip System Orientations and Grainmentioning
confidence: 99%
“…In [46], it was concluded that the criteria are applicable for hexagonal close-packed (HCP) materials, too. For body-centered cubic (BCC) materials, the existing work is still not exhaustive up to date, e.g., [13,14,47,48]. In the latter two experimental works, the minimization of the RBV was confirmed for BCC.…”
mentioning
confidence: 99%
“…12b), variation is observed between regions of similar grain size. This can be caused by differences in grain orientation [42,43] and dislocation slip transmission between grains [44,45]. The plastic zone from a hardness indentation is hemispheric, extending 1.0-1.9 times the contact radius with the highest plastic strain (>20 %) located directly underneath the indenter contact region [46].…”
Section: Diskusijamentioning
confidence: 99%